FAKTOR-FAKTOR YANG MEMENGARUHI KNOWLEDGE SHARING PADA DIVISI TEKNOLOGI INFORMASI - Diyah Utari; Semlinda Juszandri Bulan; Iklima Ermis (Universitas Muhammadiyah Ponorogo, 2017)
Competitiveness of an organization does not only base on tangible assets like current assets and fixed assets, but also intangible assets like knowledge. Knowledge Sharing is a need of a company for maintaining business entities and improving competitiveness. This study was conducted randomly against 60 employees of IT division from three companies, namely PT. Astra Internasional, tbk., PT. Nokia Siemens Network, and PT. Ericsson Indonesia, for knowing the influence factors of knowledge sharing activity in IT division. There were four variables that was used as a model, namely individual factor, organizational factor, technology factor and knowledge resource factor. The processing of research data was using multiple linear regression methode. Analysis result showed that influence factors significantly of sharing knowledge in IT division, respectively organizational factor, knowledge resource factor, individual factor and technology factor; technology factor was not highly influence of knowledge sharing in IT division (0.188); and there were impediments of knowledge sharing in IT division.